2022
DOI: 10.3390/rs14122909
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations of Forest Vegetation Phenology and Its Response to Climate Change in Northeast China

Abstract: Vegetation phenology is an important indicator of vegetation dynamics. The boreal forest ecosystem is the main part of terrestrial ecosystem in the Northern Hemisphere and plays an important role in global carbon balance. In this study, the dynamic threshold method combined with the ground-based phenology observation data was applied to extract the forest phenological parameters from MODIS NDVI time-series. Then, the spatiotemporal variation of forest phenology is discussed and the relationship between phenolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
(98 reference statements)
3
8
0
Order By: Relevance
“…Yu et al (2017) revealed that the spring phenology of Northeast China was between Julian days 100 and 140 from 1982 to 2015. Previous studies utilizing remote sensing data from Northeast China have also reported comparable outcomes (Zhao et al, 2016;Zheng et al, 2022). The consistency between these outcomes and the extracted phenological results of our study show that our study results are reliable and have a certain reference value.…”
Section: Changes In Spring Phenology Over the Past 34 Yearssupporting
confidence: 87%
See 2 more Smart Citations
“…Yu et al (2017) revealed that the spring phenology of Northeast China was between Julian days 100 and 140 from 1982 to 2015. Previous studies utilizing remote sensing data from Northeast China have also reported comparable outcomes (Zhao et al, 2016;Zheng et al, 2022). The consistency between these outcomes and the extracted phenological results of our study show that our study results are reliable and have a certain reference value.…”
Section: Changes In Spring Phenology Over the Past 34 Yearssupporting
confidence: 87%
“…Some are constrained by short study periods (Cai et al, 2012; X. J. Shen et al, 2019), impeding a comprehensive understanding of long‐term phenological changes. Others have not considered the division of the region into distinct ecogeographical areas, hindering exploration of regional disparities (Zhao et al, 2016; Zheng et al, 2022). Moreover, many studies have focused on the relationship between the SOS and climate variables solely from two perspectives (Qiao et al, 2019; Tang et al, 2015): temperature and precipitation, neglecting the influence of solar radiation in controlling SOS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third stage, volume index images based on ASTER, SRTM, and ALOS Palsar were then compared with vegetation indices of NDVI and SAVI, as well as with FCD model based on the spectral transformation of Landsat series images. These indices have been known to have strong correlation with biomass content, stand volume, and carbon storage (Margaretha et al, 2013;Dewa and Danoedoro, 2017;Pahlevi et al, 2021;Zheng et al, 2022). Prior to the application of…”
Section: Vegetation Index Transformationmentioning
confidence: 99%
“…Likewise, when remote sensing is associated with dendrochronology, the ecological mechanisms that underlie forest growth can be elucidated [23][24][25]. One of the most utilized indices is the normalized difference vegetation index (NDVI) [26,27], yet this requires further research, particularly considering the availability of automated monitoring platforms that operate in near real-time (see Google Earth Engine) [28]. In this way, the convergence of discrete variables from tree rings [10] and continuous variables from NDVI [29] exponentially increase the capacity of the results in terms of the assessment of the timing and rates of forest growth.…”
Section: Introductionmentioning
confidence: 99%